놀이권 보장 측면에서 본 국내외 어린이놀이터 관련 법제 비교 연구 - 송윤정; Song Yun-jeong; 이상민; Lee Sang-min; 강현미; Kang Hyunmi; 김수인; Kim Suin (한국조경학회지, 2023)
유엔아동권리협약은 아동이 충분한 휴식과 여가, 놀이에 참여할 수 있도록 적절하고 균등한 기회를 제공하기 위해 노력해야 함을 규정하고 있다. 이에 따라, 최근 아동의 권리 측면에서 놀이의 중요성이 지속적으로 강조되고 있으며, 놀이를 위한 시설과 공간의 필요성이 재차 언급되고 있다. 한편, 국내에서는 놀이시설의 수가 지속적으로 증가하고 있는 추세임에도 불구하고 아동의 놀이 공간에 대한 개선 노력이 요구되고 있다. 따라서 본 연구에서는 놀이 권 보장 측면에서 놀이 및 놀이공간에 대한 현행 제도와 정책에 대해 재검토하며, 국외 관련 제도와의 비교분석을 통해 제도적 시사점을 도출하고자 하였다. 국내 어린이놀이터의 법적 개념과 관련 법령, 조성 기준, 자치 조례를 분석하였으며, 영국, 캐나다, 독일의 관련 제도를 주요 특성 중심으로 분석하였다. 비교분석의 결과를 바탕으로 놀이권 보장 측면에서 어린이놀이터 제도 개선 방향을 네 가지로 제안하였다. 첫째, 어린이놀이터의 개념과 범위에 대한 법적 정의를 마련하여야 한다. 둘째, 안전관리 중심의 시설 규정을 넘어 놀이권 보장을 위한 제도적 보완이 필요하다. 셋째, 단위 시설이 아닌 공간적 개념으로서 어린이놀이터에 대한 포괄적 접근이 필요하다. 넷째, 어린이놀이터 조성과 관련된 구체적인 지침 및 가이드라인을 통해 질적 관리가 필요하다. 이러한 결과는 향후 도시계획, 아동복지, 교육 분야 등에서 놀이권 보장을 위한 제도개선을 추진함에 있어서 근거자료로써 활용될 수 있을 것이다. The importance of play from a Children's Rights perspective has been continuously emphasized, and the need for play facilities and spaces has been reiterated. Meanwhile, in South Korea, despite the continuous increase in the number of play facilities, efforts to improve children's play spaces are required. Therefore, this study reevaluated the current regulations and policies concerning play and play spaces from the perspective of securing the right to play. An analysis of the legal concept of domestic playgrounds, related laws, construction standards, and regulations was conducted. The systems and characteristics of the related regulations in the UK, Canada, and Germany were analyzed. Based on the results of the comparative analysis, our directions for improving the system of playgrounds to ensure the children’s right to play were proposed. First, a legal definition of the concept and scope of playgrounds should be established. Second, beyond safety-focused facility regulations, there is a need for institutional enhancements to ensure the right to play. Third, comprehensive management of playgrounds is required as a spatial concept rather than as individual facilities. Fourth, qualitative management is needed through specific guidelines and guidelines related to the establishment of playgrounds. These results can serve as a basis for establishing systems and promoting policy projects to ensure children's right to play in various fields, including urban planning, child welfare, and education in the future.